Fire and fury : inside the Trump White House - Wolff, Michael, 1953- (Henry Holt and Company, 2018)
Thanks to his deep access to the West Wing, Michael Wolff tells the story of the stormy first nine months of Donald Trump's term as President. Among the revelations: What President Trump's staff really thinks of him -- What inspired Trump to claim he was wire-tapped by President Obama -- Why FBI director James Comey was really fired -- Why chief strategist Steve Bannon and Trump's son-in-law Jared Kushner couldn't be in the same room -- Who is really directing the Trump administration's strategy in the wake of Bannon's firing -- What the secret to communicating with Trump is -- What the Trump administration has in common with the movie The Producers.